2019
DOI: 10.3892/ol.2019.10426
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus‑mediated RNA interference targeting programmed death receptor ligand�1 increases the immunologic anti‑tumor effect of dendritic cell vaccination against pancreatic cancer in SCID‑hu mice

Abstract: Programmed death receptor ligand 1 (PD-L1), which belongs to the B7 family, is overexpressed in a variety of human cancer types and serves a crucial role in immune escape by malignant cells. Programmed death receptor 1 (PD-1) is a specific PD-L1 receptor. PD-1/PD-L1 signaling inhibits the antitumor effects of dendritic cell (DC) immunization for tumor treatment. The aim of the present study was to determine whether inhibiting PD-L1 may increase the immunologic anti-tumor effect of dendritic cells against pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In vitro and in vivo lentivirus-based RNA silencing of PD-L1 signaling in a pancreatic cancer cell line and in SCID-hu mice with pancreatic cancer showed improved results after dendritic cell (DC) immunization. An in vitro investigation showed a cytotoxic T-cell-based antitumor response, while in vivo , lung metastasis and tumor growth in mice were inhibited and survival rates increased [ 164 ]. In one study, an integrase-defective lentiviral vector (IDLV) was engineered to express genes for the influenza virus nucleoprotein (NP) and hemagglutinin (HA), and this was used to inoculate CB6F1 mice.…”
Section: Rna Virusesmentioning
confidence: 99%
“…In vitro and in vivo lentivirus-based RNA silencing of PD-L1 signaling in a pancreatic cancer cell line and in SCID-hu mice with pancreatic cancer showed improved results after dendritic cell (DC) immunization. An in vitro investigation showed a cytotoxic T-cell-based antitumor response, while in vivo , lung metastasis and tumor growth in mice were inhibited and survival rates increased [ 164 ]. In one study, an integrase-defective lentiviral vector (IDLV) was engineered to express genes for the influenza virus nucleoprotein (NP) and hemagglutinin (HA), and this was used to inoculate CB6F1 mice.…”
Section: Rna Virusesmentioning
confidence: 99%
“…The antitumor effects of dendritic cell (DC) immunization have been observed to be inhibited by the signaling functions of PD-1/PD-L1. The shutdown of the PD-L1 expression by lentivirus-mediated RNAi in SCID-hu mice injected with human pancreatic cancer PaTu8988 cells (Wang et al, 2019), reduced the tumor growth and lung metastasis thereby increasing the survival time of SCIDhu mice. Staphylococcal nuclease domain-containing protein 1 (SND1), also termed as P100 is a major component of RISC complex which regulates gene expression at both transcriptional and translational levels.…”
Section: Lung Cancermentioning
confidence: 99%
“…Preclinical data indicated that DC vaccines combined with ICBs could generate a synergistic effect with low additional toxicity [40]. Moreover, PD-L1 knockdown by lentivirus-mediated RNA interference combined with DC vaccination may enhance T cell activity in PC on inhibiting metastasis and improving survival [41]. Furthermore, the cancer vaccine GVAX combined with anti PD-1/PD-L1 therapy increased CD8+ T infiltration into pancreatic tumors and improved patient survival [42].…”
Section: Pd-l1/pd-1 and Vaccinesmentioning
confidence: 99%